Biography Of KH, Muhammad Mansur As Islamic Education Leaders In Muara Tebo, Tebo District (1936-2002) - Aprizal Ahmad; Muh. Jafar; Hendri, Hendri; Al- Qanit Qurba; Maria Ulfa; Resva Ingriza (Cita konsultindo, 2022)
The purpose of this research was to find out the biography of KH Muhammad Mansur and to find out the education of KH Muhammad Mansur, as well as KH Muhammad Mansur's efforts in developing Islamic education . This type of research uses qualitative research in which the data is analyzed in a narrative manner using historical research methods which is a type of research that aims to systematically, accurately and objectively reconstruct incidents or events that have occurred in the past using a normative and interpretive approach. Retrieval of data using primary data and secondary data. Based on the data analysis carried out by the author, re-examines the data obtained for each question, and examines the data in depth by connecting one data to another, and draws conclusions using things that are at the heart of the results of in-depth research.